Reinforcement of Medieval infrastructure: Medieval castles and caravanserais in Aruch and Dashtadem along the Dvin-Ani transit route - Babajanyan, Astghik (ARAMAZD: Armenian Journal of Near Eastern Studies, 2024)
In the article the discussion centres on how the infrastructure along one of the transit routes of the Silk Road connecting the Armenian major city of Dvin and the capital city of Ani was organized and furnished during the high medieval period. The targeted area (a part of the historical region (gavaṛ)Aragatsotn), located between the Ararat plain and Shirak plateau, served as a transit zone for millennia. The persistent intention of the reigning Zakarid Principality to improve the infrastructure during the high medieval period is evidenced in literary, epigraphic, and numismatic sources and is clearly visible in the landscape, particularly in the construction of caravanserais, bridges, and castles that overlook the routes. The core of this paper is based on the results of excavations carried out in Aruch and Dashtadem castles, both of which are located near the caravanserais built along the transit road and share the same architectural features typical to the ones of the 12-13th centuries.